Integration of Religious Counseling in Achieving Mental Health - Maftuhah, Siti; Yulfi, Yulfi; Ardimen, Ardimen (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2024)
In life, every person will discuss various kinds of events or problems that come their way. Difficult problems and not being able to solve them have an impact on mental health. Efforts to maintain mental health have emerged as a topic that is popular with many people, apart from its important existence, mental health affects the quality of life. One of these efforts is through a religious counseling approach which can be seen in previous research literature. This research aims to find the existence of the truth to date. So, through the library research method used in this research, the aim is to look for various references and previous research results that are useful in answering existing problems as a basis for the theory being studied. And it results that the integration of spiritual and religious values in religious counseling does have a positive impact in efforts to maintain mental health as the purpose of the counseling process.